Shifting El Niño inhibits summer Arctic warming and Arctic sea-ice melting over the Canada Basin - Chundi Hu (Nature Portfolio, 2016)
Teleconnections between different flavours of El Niño and Arctic climate change are inherently uncertain in the context of warming. Here, the authors show that Central Pacific El Niño contributes to summer Arctic cooling and sea-ice increase via an Equator-Arctic teleconnection on interannual timescales.